AKAD AS-SULHU SEBAGAI INDUK PENYELESAIAN SENGKETA DALAM MU’AMALAH MENURUT IMAM JALALUDIN AS-SUYUTI - Ahmad Muflikhudin (LPPM STAI DARUSSALAM LAMPUNG, 2020)
This article aims to describe the As-Sulhu Akad as the root of dispute resolution in mu'amalah. The research method in this article was carried out by studying the literature on the works of classical scholars. The results of this study explain that dispute cases are resolved through courts (litigas), and some are resolved amicably (out of court) or non-litigation. In Islamic economic law, solving problems outside the court is termed as tahkim and As-sulhu. According to Imam Jalaludin As-Suyuti in the Asbah Wanadhoir book, it is explained that AS-Sulhu (negotiation) can include buying and selling, leasing, and accounts payable. The positive impact expected from this article is that Muslims can use the As-Sulhu Akad as a strategic step in solving problems.